Notes on Acanthoscurria chacoana Br thes, 1909 (Araneae: Theraphosidae) in Brazil, and its synonymy with Acanthoscurria altmanni Schmidt, 2003 - Bertani, Rogério; Carla-Da-Silva, Silvia (Zootaxa, 2004)
The types of Acanthoscurria chacoana, a species described from Argentina, Bolivia and Paraguay were studied and compared with Brazilian material. Spermathecal and palpal bulb morphology was found to exhibit a high degree of variability, both within and between populations. A. chacoana can be distinguished by male having a short, thickened embolus with a very long, narrow prolateral inferior keel, and female having fused spermathecae that are typically longer than wide, with their terminal receptacles close together. Its geographical distribution is extended into Brazil within and around the Pantanal Matogrossense region. The species Acanthoscurria altmanni Schmidt, 2003 is considered a junior synonym of A. chacoana.